The Concept and Essence of Specialised Knowledge Used in Smuggling Investigation - Yu. Yu. Kovalov (Bulletin of Kharkiv National University of Internal Affairs)
The article substantiates that in the theory of forensic science the concept of “special knowledge” has a broad and narrow meaning. The expediency of using this term in a narrow sense is determined by the context of its use (for example, in terms of a specific specialisation or a group of criminal offences combined on the basis of certain criminal law and/or forensically significant features). It is found that in the course of investigation of criminal offences related to smuggling, the most common is the use of specialised knowledge in the field of science, technology and art.